Stasiun Djoernatan Centraal Semarang: Sebuah Riwayat Stasiun Trem Kolonial - Mulyanto, Heru; Lubis, Dewi Afriani (UIN Sunan Gunung Djati Bandung, 2023)
Djoernatan Centraal Station, formerly known as Semarang Centraal Station, is an inactive tram station located in Purwodinatan, Central Semarang. This station used to be a large station that had quite a lot of railroad lines such as a locomotive depot, carriage depot, warehouse, and even a workshop. This station was built around the mid-1800s and was built by Samarang-Joana Stroomtram Maatschappij which was the Dutch East Indies railroad company. Djoernatan Centraal Station was the center of the Semarang City steam tram network at that time. Apart from connecting the Djoernatan Centraal station with the Semarang NIS Station (Kemijen Station) in Tambaksari and the Port of Semarang, this city tram also takes the Jurnatan-Bulu and Jurnatan-Jomblang routes. The Jurnatan–Bulu route is on the side of Jalan Bojong (Youth Street) while the Jurnatan–Jomblang route runs along the road which is now known as Jalan MT Haryono. This tram line was closed in 1940 due to unprofitability and all remaining locomotives and carriages were moved to Surabaya. This research reveals the development of the Djoernatan Centraal station since the beginning of its construction, its management, and the period when this station ended and closed.Keywords: Jurnatan Station, Tram Station, Semarang-Joana Stroomtram Maatschappij, Development of the station.